Antioxidant Actions of Thymoquinone, Silymarin, and Curcumin on Experimental Aortic Ischemia-Reperfusion Model in Wistar Albino Rats - Yardımcı,Mustafa (2022)
ABSTRACT Introduction: Medical improvements are needed to prevent ischemia-reperfusion injury in thoracoabdominal aortic surgery. The aim of this study was to determine the antioxidant effects of thymoquinone, silymarin, and curcumin against ischemia-reperfusion injury associated with abdominal aorta. Methods: Twenty-five Wistar albino rats were included in the study. Sham, control, and treatment (thymoquinone, silymarin, and curcumin) groups were set in equal numbers. Ischemia-reperfusion was applied by clamping (120 minutes) and de-clamping (60 minutes) the infrarenal aorta of all groups, except the sham group. Before reperfusion, thymoquinone, silymarin, and curcumin were given intraperitoneally to the treatment groups. After reperfusion, blood samples were taken from the right ventricle. Total antioxidant status (TAS), total oxidant status (TOS), and oxidative stress index (OSI) were studied in serum samples and histopathological examination was performed on the gastrocnemius muscle. Results: There was a significant difference in TOS and OSI values between the control and sham groups. Both values were found higher in the control group than in the sham group (P<0.05). OSI values were found to be lower in the thymoquinone group compared to the control group (P<0.05). All three parameters were found to be lower in the silymarin group than in the control group (P<0.05). TAS and TOS levels were found to be higher in the curcumin group than in the control group (P<0.05). There was no histopathological difference between the groups. Conclusion: Silymarin and thymoquinone administration decreases oxidative stress in experimental aortic ischemia-reperfusion injury. Antioxidant effect of curcumin was lower than silymarin and thymoquinone.